Exemplary in The Qur'an and Its Implementation with Islamic Education - Taklimudin Taklimudin; Idi Warsah; Sumarto Sumarto; Nurjannah Nurjannah (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2022)
Based on the current phenomenon, children are experiencing a crisis of exemplary because the lack of mass media that raises the theme of role models for children, for example the television  are dominated by entertainment programs variations such operas or celebrity gossip which cannot be expected to provide a complete example of life. In this exemplary crisis, the educators are an important basis. Therefore, educators must have high awareness, to be role models in the process of forming children's Islamic character. The results of this study prove that: exemplary in education is an effective method/way in preparing children in terms of morals, mental and social. Psychologically exemplary is applied as a method of Islamic education because basically humans since childhood have had a desire to imitate the movements or behavior of parents, teachers, and the environment. Based on the case parents and teachers have to have exemplary qualities as practiced by the Prophet. such as patience, compassion, morality, tawadhu ', zuhud and fair.